2017
DOI: 10.5152/turkpediatriars.2017.4254
|View full text |Cite
|
Sign up to set email alerts
|

Research of genetic bases of hereditary non-syndromic hearing loss

Abstract: Aim: Hearing loss is the most common sensory disorder that affects approximately one per 1000 live births. With this project, we aimed to identify gene variants that were common causes of hearing loss in Turkey to contribute to the planning of genetic screening programs for hearing loss, as well as to improve genetic counseling to affected families. Material and Methods: Twenty-one families with at least two affected individuals and parental consanguinity who presented with non-syndromic severe-to-profound sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Taken together with the high ratio of compound heterozygosity, this finding suggests that ARNSHL is a health problem not restricted to consanguineous marriages. Some GJB2 mutations reported previously from Turkey were not found in our patient cohort (32). These variants include c.360_362delGAT (p.delE120), c.310_323del14, c.299_300delAT, c.517C>T (p.P173S) and c.238C>A (p.Q80K).…”
Section: Discussionmentioning
confidence: 50%
“…Taken together with the high ratio of compound heterozygosity, this finding suggests that ARNSHL is a health problem not restricted to consanguineous marriages. Some GJB2 mutations reported previously from Turkey were not found in our patient cohort (32). These variants include c.360_362delGAT (p.delE120), c.310_323del14, c.299_300delAT, c.517C>T (p.P173S) and c.238C>A (p.Q80K).…”
Section: Discussionmentioning
confidence: 50%
“…The frequency of p.R84W was reported by 10.3% and 2.4% in Southeastern Anatolia and Turkey, respectively 30,31 . Haplotype analysis showed that the mutation was due to a ‘Founder Effect’ since approximately 1250 years ago.…”
Section: Transmembrane Inner Earmentioning
confidence: 99%
“…The improved diagnostic, prognostic, and therapeutic options are the potential translational outcomes of systematic elucidation of NSHL genes [4]. Involvement of gene-encoded proteins in hearing function is expected because the inner ear and hearing mechanism has a very complicated structure [11]. Thus, the present study has focused on exploring some other target genes and most deleterious mutations in genes other than GJB2, which might lead to genetic NSHL through systematic review since the last decade (2009-2020) and in silico analyses like functional network analysis and variant study.…”
Section: Introductionmentioning
confidence: 99%